The role of vibrato in the perception of violin timbral quality - Law, Michele Soo Ling (2002)
This research seeks to verify the assumption that the presence of vibrato assists listeners in "hearing" the resonance structure of a violin, hence facilitating judgments concerning violin timbral quality. Three violins of different costs and presumably different qualities were used. Listening tests were conducted to identify the perceived timbral quality of each violin. To further validate the results, body resonance curves of the violins were analyzed based upon the location and separation of two major resonance peaks. The results obtained were compared with those of previous research findings to confirm the quality of each violin. Spectrum analysis on glissando tones provided data for the plotting of the resonance curves. A pitch and vibrato detection algorithm using interpolated zero crossings was tested for its ability 10 accurately extract the quantifiable parameters of a vibrato. namely its rate and frequency excursion.